Carbon nanotube-reinforced aluminum composite produced by induction melting - Mansoor, Muhammad; Shahid, Muhammad (Journal of applied research and technology, 2016)
Aluminum/carbon nanotube composite is a promising candidate material for aerospace applications owing to its high strength-to-weight ratio. Because of the low density of carbon nanotubes (CNTs), their dispersion is difficult in molten metal. We investigated induction melting, a fairly distinct approach to facilitate the dispersion of CNTs in molten aluminum. The nanocomposites were characterized using scanning electron microscopy, X-ray diffraction, transmission electron microscopy and mechanical testing. Refinement in crystallite size (∼320nm) and increase in lattice strain (∼3.24×10−3) were observed in the composites. A simultaneous increase in yield strength (∼77%), tensile strength (∼52%), ductility (∼44%) and hardness (∼45%) was observed. Induction melting appeared to be a potential method to fabricate aluminum–CNTs composites.